Stability of Bradyrhizobium japonicum Inoculants after Introduction into Soil - Brunel, Brigitte (1988)
Bradyrhizobium japonicum USDA 125-Sp, USDA 138, and USDA 138-Sm had been used as inoculants for soybean (Glycine max (L.) Merr.) in soils previously free of B. japonicum. At 8 to 13 years after their release, these strains were reisolated from soil samples. A total of 115 isolates were obtained through nodules, and seven colonies were obtained directly by a serological method. The stability of the inoculants was confirmed by comparing the reisolated cultures with their respective parental strains which had been preserved by being lyophilized or stored on a yeast extract-mannitol agar slant at 4°C. Comparisons were made on morphological and serological characters, carbon compound utilization (8 tested), intrinsic antibiotic resistance (9 tested), and enzymatic activity (19 tested). Mucous and nonmucous isolates of serogroup 125 were analyzed for symbiotic effectiveness and restriction fragment hybridization with a DNA probe. Our data suggest that the B. japonicum inoculants have survived for up to 13 years in the soils without significant mutation except for two reisolates with a slightly increased kanamycin resistance level.